Network disruption detected in UG (Uganda) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Uganda. Data sourced from CensoredPlanet, IODA.
Censorship Incident ID: UG-2026-0002. Severity: critical. Confidence: 70%